A386G polymorphism of the DAZL gene is not associated with idiopathic male infertility in North India - Kiran Singh; Rajiva Raman (Wolters Kluwer Medknow Publications, 2009)
Background: Male infertility is a multifactorial disorder which affects approximately 10% of couples at childbearing age with substantial clinical and social impact. Genetic variation and environmental factors contribute to susceptibility to spermatogenic impairment in humans. The A386G (T54A) polymorphism of the autosomal gene, DAZL, has shown susceptibility to spermatogenic failure in Taiwanese population. However, no such association has been seen in infertile patients from Italy and South India. Aim: This study aims to find out the possible association between A386G (T54A) polymorphism of the autosomal gene, DAZL and idiopathic male infertility in patients from North India. DESIGN: Case-control study. Materials and Methods: The prevalence of A386G (T54A) polymorphism was determined in 165 idiopathic infertile azoo-/oligospermic patients and 200 fertile healthy control men. PCR-RFLP analysis was employed to determine the genotypes. PCR amplicons were subjected to restriction digestion with AluI as this mutation created a restriction site (AGCT), and separated on a 12% polyacrylamide gel. Results: Analysis of 165 idiopathic infertile azoo-/oligospermic and 200 fertile control men revealed only one case of the variant as a heterozygote in the control population. Single Nucleotide Polymorphism (SNP) was absent in the infertile patients. Conclusion: As in the report from Italy and South India, our results illustrate the rarity of this mutation. Apparently, this mutation is of recent origin and/or has poor selective value. Its preponderance in infertile patients from Taiwan (all heterozygotes) suggests a founder effect and also that its low selective value could be due to impaired spermatogenesis.